A 1204-single nucleotide polymorphism and insertion–deletion polymorphism panel for massively parallel sequencing analysis of DNA mixtures. (January 2018) - Hwa, Hsiao-Lin; Chung, Wan-Chia; Chen, Pei-Lung; Lin, Chih-Peng; Li, Huei-Ying; Yin, Hsiang-I; Lee, James Chun-I
Highlights: A 1204-mark panel for massively parallel sequencing was developed. This panel consists autosomal, X-, Y-, and mitochondrial SNP/indels. A scoring system for MPS data was developed for minor contributor identification. The minor donors in nondegraded/degraded DNA mixtures were identified accurately. Abstract: Massively parallel sequencing (MPS) technology enables the simultaneous analysis of a huge number of single nucleotide polymorphisms (SNPs) and insertion–deletion polymorphisms (indels). MPS also enables the detection of the alleles of minor contributors in a highly unbalanced DNA mixture. In this study, we established a 1204-marker panel optimized for MPS consisting of 987 autosomal markers (964 SNPs and 23 indels), 27 X-chromosome SNPs, 61 Y-chromosome markers (56 SNPs and 5 indels), and 129 mitochondrial SNPs. The DNA samples of six unrelated individuals (two men and four women), 26 nondegraded DNA mixtures (with minor to major ratios of 1:29, 1:39, 1:79, and 1:99), and eight highly artificially degraded DNA mixtures (with minor to major ratios of 1:29, 1:39, 1:79, and 1:99) were analyzed through MPS by using the panel. A scoring system was developed to determine the minor contributors in DNA mixtures based on the genotypes identified using MPS. The genotypes of the 1204 markers were successfully profiled through MPS by using the custom-designed panel. The efficiency of MPS for analyzing these highly degraded samples was lower than that for analyzing nondegraded samples. All minor contributors in the 26 nondegraded and 8 degraded DNA mixtures were accurately assigned using this scoring system based on 964 autosomal SNPs. An association between the observed reads ratio and theoretical ratio of the minor component was noted for nondegraded mixtures. In conclusion, we established a 1204-marker individual identification panel for MPS that successfully analyzed autosomal, X-chromosome, Y-chromosome, and mitochondrial SNPs and indels simultaneously. In combination with the newly developed scoring system, the panel can accurately identify minor contributors in nondegraded and highly degraded DNA mixtures.